2014
DOI: 10.1371/journal.pone.0100318
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Emotional Responses to Cooperative and Competitive Game Play

Abstract: Previous research indicates that males prefer competition over cooperation, and it is sometimes suggested that females show the opposite behavioral preference. In the present article, we investigate the emotions behind the preferences: Do males exhibit more positive emotions during competitive than cooperative activities, and do females show the opposite pattern? We conducted two experiments where we assessed the emotional responses of same-gender dyads (in total 130 participants, 50 female) during intrinsical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 77 publications
(123 reference statements)
1
54
1
2
Order By: Relevance
“…Furthermore, evolutionary psychology suggests that, in this regard, humans have evolved positive emotions to facilitate survival through cooperation, and negative emotions to defend against those who do not cooperate (e.g., Petersen, Sznycer, Cosmides, & Tooby, 2012). Consequently, competition should elicit more negative emotions than cooperation (Kivikangas, Kätsyri, Järvelä, Ravaja, & Pavlova, 2014). An EMG study supports this statement by finding that the expectations of cooperation activated the muscles that respond in a smile and the expectation of competition activated the muscles that respond in a grimace (Lanzetta & Englis, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, evolutionary psychology suggests that, in this regard, humans have evolved positive emotions to facilitate survival through cooperation, and negative emotions to defend against those who do not cooperate (e.g., Petersen, Sznycer, Cosmides, & Tooby, 2012). Consequently, competition should elicit more negative emotions than cooperation (Kivikangas, Kätsyri, Järvelä, Ravaja, & Pavlova, 2014). An EMG study supports this statement by finding that the expectations of cooperation activated the muscles that respond in a smile and the expectation of competition activated the muscles that respond in a grimace (Lanzetta & Englis, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Social-evaluative threat is inherent in competitions as participants are compared along a common dimension that is often relevant for self-esteem. Indeed, increases in the stress hormone cortisol as well as in markers of sympathetic nervous system activity like blood pressure, heart rate, and alpha-amylase have been observed in reaction to sports competitions (e.g., Rohleder et al 2007; Kivlighan and Granger 2006;Cooke et al 2011), during video game playing (Harrison et al 2001;Kivikangas et al 2014;Veldhuijzen Van Zanten et al 2002), and in response to motoric and cognitive tasks which were carried out in a competitive manner (Wittchen et al 2013;Turner et al 2012;Hatfield et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In the classic Vinacke's (1969) studies of triad coalitions, it was found that girls applied less risky strategies and made unnecessary coalitions to achieve success. This same imbalance, favoring competition on cooperation of the boys was confirmed (Kivikangas et al, 2014) by the girls showing themselves to be more balanced in the cooperation-competition binomial.…”
Section: Discussionmentioning
confidence: 56%
“…The boys, when selecting their game solutions, have followed the most important strategic motive, to win, which is the most advantageous solution as a game achievement. Keeping the distances, this same strategic advantageous solution is behind the attraction for the rivalry to which Kivikangas et al (2014) alluded in boys. Also, in a context of motor play, greater proportions of male protagonism and ball throws (Gutiérrez and García-López, 2012) were identified.…”
Section: Discussionmentioning
confidence: 99%